Traceability of horticultural produce in Kenya: Situation and trajectory - Hoffmann, Vivian (International Food Policy Research Institute, 2019)
Traceability means it is possible to trace food back to its origin. If consumers become ill from the food they have eaten, or food is found to contain a harmful chemical, traceability allows this food to be traced from the shop where it was purchased, to the trader who delivered it, to the factory that processed or packed it, and ultimately to the farm where it was grown. In this way, the source of the problem can be identified and corrected [1]. Traceability is considered a fundamental component of modern food safety systems.